Fretting initiated crevice corrosion of 316LVM stainless steel in physiological phosphate buffered saline: Potential and cycles to initiation. (1st October 2019) - Liu, Yangping; Zhu, Dongkai; Pierre, David; Gilbert, Jeremy L.
Graphical abstract: Abstract: Mechanically assisted crevice corrosion (MACC) has been associated with implant failure in vivo and is a serious concern in numerous metallic implant systems. Stainless steel medical devices may be subjected to fretting and crevice corrosion in the human body as are titanium and CoCrMo alloys due to the presence of a passive oxide film on their surface. One mechanism of MACC that has not been clearly identified and studied is fretting-initiated crevice corrosion (FICC) of stainless steel where an initial fretting event can initiate a rapid propagating crevice corrosion process even when fretting has ceased. FICC pin-on-disk experiments were performed at varying potential conditions and duration of fretting to explore the role of potential and fretting duration on the initiation of crevice corrosion. Triggering of a propagating crevice corrosion reaction on stainless steel at 250 mV vs Ag/AgCl/KCl (saturated) in PBS solution required only 2 s (2 cycles at 1 Hz) of fretting. Crevice corrosion continued to propagate under a 1.8 mm diameter pin with only 100 μm of direct contact, dissolving in both the depth and width dimension away from the fretting contact while the currents rose from 0.2 μA to 15 μA within 5 min. Three different potential-dependent FICC regions were identified that included unstable crevice corrosion (50 mV and above), metastable crevice corrosion (−100 mV to 0 mV) and stable fretting corrosion (between −500 mV and −150 mV). Crevice corrosion can be induced by fretting at potentials as low as −100 mV. Below −100 mV, there was no FICC, but rather fretting corrosion stopped immediately after fretting ceased and returned to a stable baseline current. Metastable FICC was shown at potentials between −100 mV and 0 mV, when the crevice corrosion current gradually decreased over several seconds or longer after fretting ceased. Self-sustained, unstable crevice corrosion started at 50 mV, where prior to fretting the currents were low, and after just a few cycles of fretting the crevice current rose rapidly and continued to increase after fretting stopped. Increase of potential increased the susceptibility of stainless steel to FICC. Scanning electron microscopy and digital optical microscopy revealed pitting and crevice corrosion on samples at −100 mV and higher potentials, where FICC was developing. By removing the oxide film, fretting motion significantly facilitates the critical crevice solution development, lowering the critical crevice potential and decreasing the initiation time for crevice corrosion. These results indicate that fretting initiated crevice corrosion may affect the performance of stainless steel in vivo . Statement of Significance: AISI 316L stainless steel has been widely used as a metallic biomaterial for orthopaedic, spinal, dental and cardiovascular implants. Crevice corrosion has been a serious concern for stainless steel implants. For the first time we demonstrated and systematically studied the process of fretting-initiated crevice corrosion (FICC) in 316L stainless steel in simulated physiological solution of phosphate buffered saline. By removing the oxide film, fretting motion significantly facilitates the critical crevice solution development, lowering the critical crevice potential and decreasing the initiation time for crevice corrosion. Our findings indicate fundamental differences between the FICC mechanism and conventional crevice corrosion theory, showing that fretting can play a significant role in the initiation of crevice corrosion of stainless steel.